The epidemiology and prognosis of patients with primary gastric T‐cell lymphoma in the SEER program. (13th June 2022) - Zhang, Minyue; Xiao, Fei; Lin, Meisi; Chen, Mengping; Hou, Jian; Huang, Honghui
Abstract: Background: Primary gastric T‐cell lymphoma (PG‐TCL) is a rare hematological malignancy with few data reported. The objective of this study is to investigate the epidemiology, clinical characteristics, and survivals of PG‐TCL. Methods: Totally, 164 patients with PG‐TCL from 1975 to 2016 extracted from the Surveillance, Epidemiology, and End Results Program (SEER) database were analyzed. Kaplan–Meier method was applied to plot overall survival (OS) and cancer‐specific survival (CSS). The prognostic factors of OS and CSS were explored by Cox proportional hazard regression. Nomograms were constructed to predict survival possibilities. Results: The age‐adjusted incidence rate of PG‐TCL was 0.0091 per 100, 000 person‐years and increased with age. The median age at onset was 65 years old with male predominance. The major histological type was peripheral T‐cell lymphoma, NOS (63.4%). The 1‐, 2‐, and 5‐year OS were 45.5%, 34.7%, and 23.5%, respectively while the 1‐, 2‐, and 5‐year CSS were 47.4%, 37.3%, and 29.6%, respectively. Multivariate Cox analysis demonstrated that age at diagnosis, use of chemotherapy, and radiotherapy were the independent prognostic factors for OS. Chemotherapy combined with radiotherapy could significantly improve patients' OS compared with chemotherapy alone. Moreover, age at diagnosis and use of chemotherapy were also the independent prognostic factors for CSS. Nomograms for PG‐TCL were developed to predict 1‐, 2‐, and 5‐year OS possibilities. The predictability of nomograms was verified by high concordance index and good agreement with the predicted value in calibration plots. Conclusion: PG‐TCL is a rare neoplasm with low incidence. Patients with PG‐TCL generally exhibited poor prognosis. Use of chemotherapy plus radiotherapy was associated with favorable OS. Abstract : This is the first and largest population‐based study about primary gastric T‐cell lymphoma(PG‐TCL). Patients with PG‐TCL generally exhibited poor prognosis. Use of Chemotherapy plus radiotherapy was associated with favorable survival.